Antimicrobial Effects of AH26 Sealer/Antibiotic Combinations Against Enterococcus Faecalis - Razmi, Hasan; Ashofteh Yazdi, Kazem; Jabalameli, Fereshteh; Parvizi, Shaghayegh (Iranian Endodontic Journal, 2009)
INTRODUCTION: The purpose of this in vitro study was to evaluate the antimicrobial effects of two antibiotics added to AH26 sealer against Enterococcus faecalis (EF). MATERIALS AND METHODS: The antimicrobial effects of two antibiotic (amoxicillin and doxycycline) that were added separately to AH26 sealer was evaluated by using the agar diffusion test and in vitro human root inoculation method. The freshly mixed sealers were placed in prepared wells inside agar plates inoculated with EF, and were incubated at 37°C. The zones of inhibition were measured at 24, 48, 72 hours and 7 days. Root specimens were prepared and obturated with lateral condensation technique. Samples were collected from infected root canals after 2 and 7 days of incubation and the number of colony-forming units (CFU) was determined. The data were analyzed using one-way and two-way ANOVA. RESULTS: The findings of this study revealed that sealer-antibiotic combination containing amoxicillin and doxycycline had a significant difference in the mean zones of inhibition when compared to AH26 sealer alone in all of the time periods (P<0.05). The minimum effective concentration against EF was one percent of sealer powder weight for both of amoxicillin and doxycyline. The mean log10 CFU in AH26-doxycyline combination group was significantly lower than other groups at 48 h incubation period (P<0.05). AH26-doxycycline combination group and AH26-Amoxicillin combination group killed bacteria (mean CFU=0) in the dentinal tubules at 7 days incubation period. CONCLUSION: In vitro root fillings carried out with gutta-percha and AH26-antibiotic combination were effective in killing EF in dentinal tubules.